PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR KRIYA KERAMIK DI SMK NEGERI 8 PADANG - BELLA EKA PRATIWI, Drs. Wisdiarman, M.Pd., Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2017)
This research aims to understand the influence of audio visual media to the result of learning pottery crafting in SMK Negeri 8 Padang. This research tested the hypothesis to know is there a significant difference in the result of learning pottery crafting taught by using audio visual media and conventional media. The population is all of the pottery crafting students. The sample is the students of class XI pottery crafting. The technique of sampling is purposive sampling. The type of research is quasi experiment with research plan is Pretest-Posttest Control Group Design. The data is collected by testing the learning result. Then, data will be analyzed by using Uji-t.The result shows : the learning result of pottery crafting that has been taught using audio visual media is difference with the result of learning by using conventional media.Based on the result of the research, we can conclude that audio visual media has positive influence towards students’s learning result in pottery crafting subject. Therefore, the audio visual media is really good to use continuosly by the teacher in the learning process in order to improve the students’s learning result specifically in pottery crafting subject in SMK Negeri 8 padang.Keywords : audio visual media, students’s learning result.